Copper-based monatomic catalyst and preparation method and application thereof
By preparing copper-based single-atom catalysts, the insufficient research problem of HMF electrochemical reduction in the field of biomass electrocatalytic conversion was solved, and the catalytic effect of efficient, selective and stable HMF conversion to DHMF was achieved.
Patent Information
- Application Number
- CN202510063907.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-03-14
AI Technical Summary
In the field of electrocatalytic conversion of biomass, there are few researches on the electrochemical reduction of HMF in the prior art, and there is a lack of a copper-based single-atom catalyst that can effectively promote the conversion of HMF to DHMF.
The copper-based single-atom catalyst was prepared by dissolving 1,10-phenanthroline and copper nitrate trihydrate in anhydrous ethanol, adding carbon black and stirring in an oil bath, then removing the ethanol and calcining, and finally etching with a mixed acid solution.
The prepared copper-based single-atom catalyst has a clear and uniform activity center and maximum metal utilization, which can efficiently catalyze the electrochemical reduction of HMF at low potentials to generate DHMF, with high reduction activity, selectivity and stability.
Smart Images

Figure CN119615242A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of catalysts for biomass electrocatalytic conversion, in particular to a copper-based single-atom catalyst and a preparation method and application thereof. Background Art
[0002] In recent years, with the rapid development of social economy, the demand for traditional fossil energy has been growing, and its non-renewable nature has led to a shortage of energy and chemical supplies. At the same time, the wastewater containing a large amount of heavy metals and harmful substances produced during the mining process and the large amount of harmful gases released during the combustion process also pose a threat to the ecological environment. Therefore, it is of great strategic significance to explore a green and clean energy that can replace traditional fossil products and is renewable. Biomass is the only renewable carbon resource in nature. It has the advantages of wide distribution, rich resources, and low pollution. Therefore, the research and development of this type of renewable resource has broad prospects.
[0003] Among these renewable resources, 5-hydroxymethylfurfural (HMF), as a biomass-based platform compound, is a bridge between biomass raw materials and high value-added chemicals. Among them, 2,5-furan dimethanol (DHMF), as an important reduction product, is an important monomer for the synthesis of fine chemicals, new functional polyethers and polyurethane foams. Therefore, the development of green, efficient and sustainable electrochemical hydrogenation reactions to generate high-value derivatives is of great significance to current scientific research and industrial production of high-value utilization of biomass.
[0004] The key to achieving high electrochemical activity hydrogenation of HMF is to rationally design a catalyst to selectively reduce the aldehyde functional group of HMF to hydroxymethyl. However, the active site of the catalyst and the intrinsic mechanism of catalysis are still worth exploring. Among them, the single-atom catalyst with a clear structure as the active center has a uniform structure of the catalytic active site, which greatly improves the process of studying the catalyst structure and provides the possibility of exploring the reaction pathway. For example, the research paper ("Electrocatalytic hydrogenation of 5-Hydroxymethylfurfural promoted by aRu1Cu single-atom alloy catalyst", Angewandte Chemie International Edition, Vol. 61, No. 37, 2022) reported the successful preparation of a Ru1Cu single-atom alloy catalyst (Ru1Cu SAA). At the same time, under the condition of adding 20mM HMF, HMF was efficiently converted to DHMF at a lower potential. It was further proved that single-atom Ru promoted the dissociation of water to produce H*, and then the possible electrochemical reduction mechanism of HMF on Ru1Cu was inferred.
[0005] However, there are few studies on single-atom catalysts in the field of biomass electrocatalytic conversion. Based on the current progress and inspiration of single-atom catalysts in electrocatalytic HMF reduction, it is urgent to develop a Cu single-atom catalyst for the electrochemical reduction of HMF to DHMF to enhance the understanding of reaction intermediates and reaction sites at the molecular level. Summary of the invention
[0006] In order to solve the above technical problems, the present invention provides a copper-based single-atom catalyst and a preparation method and application thereof.
[0007] To achieve the above object, the present invention is implemented according to the following technical solutions:
[0008] One of the technical solutions of the present invention is a method for preparing a copper-based single-atom catalyst, comprising the following steps:
[0009] S1. Dissolve 1,10-phenanthroline and copper nitrate trihydrate in a molar ratio of 3:1 in 30 mL of anhydrous ethanol and stir thoroughly to form a uniform solution. Stir magnetically in a 50°C oil bath for 3 h. Then, add 0.0300 g of carbon black to the solution and continue stirring magnetically in a 50°C oil bath for 3 h.
[0010] S2, removing ethanol from the sample obtained in step S1 and drying it, grinding the obtained solid powder into a uniform powder, calcining it at 550-750° C. for 2 h, and then cooling it to room temperature;
[0011] S3. Etching the sample obtained in step S2 with a mixed acid solution to remove unstable metal particles, filtering, washing and drying the acid-washed solution to obtain a solid powder, calcining it at 550-750° C. for 2 hours, and then cooling it to room temperature to obtain a copper-based single-atom catalyst.
[0012] Furthermore, in the step S2, calcination is carried out in an argon calcination atmosphere, and the argon flow rate is 60 sccm.
[0013] Furthermore, in step S2, the temperature is increased to 550-750°C at a heating rate of 10°C / min.
[0014] Furthermore, the mixed acid solution is a mixed solution of hydrochloric acid and nitric acid in a molar ratio of 1:2.
[0015] The second technical solution of the present invention is a copper-based single-atom catalyst prepared by the above method.
[0016] The third technical solution of the present invention is the use of a copper-based single-atom catalyst in the electrochemical reduction of 5-hydroxymethylfurfural HMF to prepare 2,5-furan dimethanol DHMF.
[0017] Compared with the prior art, the copper-based single-atom catalyst prepared by the present invention has clear and uniform active centers and maximum metal utilization, can be used for electrocatalytic reduction of 5-hydroxymethylfurfural HMF to prepare 2,5-furan dimethanol DHMF, has high reduction activity, selectivity and stability in actual catalytic reactions, and has important application value. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is a diagram of the preparation process of the copper-based single-atom catalyst of the present invention.
[0019] Figure 2 The scanning electron microscope images of the catalyst samples obtained at different calcination temperatures according to the examples of the present invention are as follows: (a) is the catalyst sample of Example 2, (b) is the catalyst sample of Example 1, (c) is the catalyst sample of Example 3, and (d) is the catalyst sample of Example 4.
[0020] Figure 3 The XRD diagrams of catalyst samples obtained at different calcination temperatures in the examples of the present invention.
[0021] Figure 4 HAADF-STEM and Mapping images of the catalyst sample of Example 1 of the present invention: (a) is the HAADF-STEM scan of the catalyst sample, and (b) is the Mapping scan of the catalyst sample.
[0022] Figure 5 LSV curves of the catalyst samples prepared in Examples 1-3 of the present invention in a boric acid electrolyte containing 0.02 M HMF.
[0023] Figure 6 The ECH conversion, selectivity and Faraday efficiency of HMF of the catalyst samples prepared in Examples 1-3 of the present invention at a potential of -0.6 V vs. RHE. DETAILED DESCRIPTION
[0024] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments. The specific embodiments described herein are only used to explain the present invention and are not used to limit the invention.
[0025] Example 1
[0026] Reference Figure 1 , 1) First, 1,10-phenanthroline and copper nitrate trihydrate in a molar ratio of 3:1 were dissolved in 30 mL of anhydrous ethanol and stirred thoroughly to form a uniform solution, and magnetically stirred for 3 h in a 50°C oil bath, and then 0.0300 g of carbon black was added to the above solution, and magnetic stirring was continued in a 50°C oil bath for 3 h;
[0027] 2) removing ethanol from the sample obtained in step 1) and drying it, grinding the obtained solid powder into a uniform powder, placing it in a quartz boat, and placing it in a tube furnace, heating the tube furnace from room temperature to 650° C. at a heating rate of 10° C. / min under an argon calcination atmosphere, pyrolyzing it at high temperature for 2 h, and then cooling it to room temperature;
[0028] 3) The sample obtained in step 2) is etched with a mixed solution of hydrochloric acid and nitric acid in a molar ratio of 1:2 to remove unstable metal particles. The acid-washed solution is filtered, washed and dried to obtain a solid powder, which is then placed in a quartz boat and placed in a tubular furnace. The tubular furnace is heated from room temperature to 650°C at a heating rate of 10°C / min in an argon calcination atmosphere. After high-temperature pyrolysis for 2 hours, it is cooled to room temperature to obtain a copper-based single-atom catalyst sample Cu-NC-650.
[0029] Example 2
[0030] Reference Figure 1 , 1) First, 1,10-phenanthroline and copper nitrate trihydrate in a molar ratio of 3:1 were dissolved in 30 mL of anhydrous ethanol and stirred thoroughly to form a uniform solution, and magnetically stirred for 3 h in a 50°C oil bath, and then 0.0300 g of carbon black was added to the above solution, and magnetic stirring was continued in a 50°C oil bath for 3 h;
[0031] 2) removing ethanol from the sample obtained in step 1) and drying it, grinding the obtained solid powder into a uniform powder, placing it in a quartz boat, and placing it in a tube furnace, heating the tube furnace from room temperature to 550° C. at a heating rate of 10° C. / min under an argon calcination atmosphere, pyrolyzing it at high temperature for 2 hours, and then cooling it to room temperature;
[0032] 3) The sample obtained in step 2) is etched with a mixed solution of hydrochloric acid and nitric acid in a molar ratio of 1:2 to remove unstable metal particles. The acid-washed solution is filtered, washed and dried to obtain a solid powder, which is then placed in a quartz boat and placed in a tubular furnace. The tubular furnace is heated from room temperature to 550°C at a heating rate of 10°C / min in an argon calcination atmosphere. After high-temperature pyrolysis for 2 hours, it is cooled to room temperature to obtain a copper-based single-atom catalyst sample Cu-NC-550.
[0033] Example 3
[0034] Reference Figure 1 , 1) First, 1,10-phenanthroline and copper nitrate trihydrate in a molar ratio of 3:1 were dissolved in 30 mL of anhydrous ethanol and stirred thoroughly to form a uniform solution, and magnetically stirred for 3 h in a 50°C oil bath, and then 0.0300 g of carbon black was added to the above solution, and magnetic stirring was continued in a 50°C oil bath for 3 h;
[0035] 2) removing ethanol from the sample obtained in step 1) and drying it, grinding the obtained solid powder into a uniform powder, placing it in a quartz boat, and placing it in a tube furnace, heating the tube furnace from room temperature to 750° C. at a heating rate of 10° C. / min under an argon calcination atmosphere, pyrolyzing it at high temperature for 2 h, and then cooling it to room temperature;
[0036] 3) The sample obtained in step 2) is etched with a mixed solution of hydrochloric acid and nitric acid in a molar ratio of 1:2 to remove unstable metal particles. The acid-washed solution is filtered, washed and dried to obtain a solid powder, which is then placed in a quartz boat and placed in a tubular furnace. The tubular furnace is heated from room temperature to 750°C at a heating rate of 10°C / min in an argon calcination atmosphere. After high-temperature pyrolysis for 2 hours, it is cooled to room temperature to obtain a copper-based single-atom catalyst sample Cu-NC-750.
[0037] Comparative Example 1
[0038] 1) First, an equal amount of 1,10-phenanthroline in the above example was dissolved in 30 mL of anhydrous ethanol and stirred thoroughly to form a uniform solution, and magnetically stirred in a 50° C. oil bath for 3 h. Subsequently, 0.0300 g of carbon black was added to the above solution, and magnetically stirred in a 50° C. oil bath for 3 h.
[0039] 2) removing ethanol from the sample obtained in step 1) and drying it, grinding the obtained solid powder into a uniform powder, placing it in a quartz boat, and placing it in a tube furnace, heating the tube furnace from room temperature to 650° C. at a heating rate of 10° C. / min under an argon calcination atmosphere, pyrolyzing it at high temperature for 2 h, and then cooling it to room temperature;
[0040] 3) The sample obtained in step 2) is etched with a mixed solution of hydrochloric acid and nitric acid in a molar ratio of 1:2 to remove unstable metal particles. The acid-washed solution is filtered, washed and dried to obtain a solid powder, which is then placed in a quartz boat and placed in a tubular furnace. The tubular furnace is heated from room temperature to 650°C at a heating rate of 10°C / min under an argon calcination atmosphere, and the catalyst sample NC is obtained after high-temperature pyrolysis for 2 hours and then cooled to room temperature.
[0041] The catalyst samples prepared in Examples 1 to 3 and the comparative example were respectively scanned by electron microscope. The scanning electron microscope images are shown in FIG. Figure 2 As shown by Figure 2 It can be seen that the morphology of the catalyst samples Cu-NC prepared in Examples 1 to 3 is consistent with that of the catalyst sample NC prepared in Comparative Example 1, and the uniform particle size and particle morphology of the original carbon black are maintained.
[0042] The XRD patterns of the catalyst samples prepared in Examples 1 to 3 and Comparative Examples are as follows: Figure 3 As shown by Figure 3It can be seen that the incorporation of Cu did not change the basic structure of the carbon support. No diffraction peaks related to metal Cu appeared in the spectrum, indicating that there were no Cu nanoparticles in the sample and it was well dispersed.
[0043] The XRD pattern of the catalyst sample prepared in Example 1 is as follows: Figure 4 As shown, Figure 4 The isolated white Cu atoms in (a) indicate that the bright spots on the surface of the carbon material are highly dispersed single atoms, confirming the atomic dispersion of Cu. Figure 4 In (b), the high-density C and N elements and the low-density Cu element are evenly distributed, and the Cu, N and C signals are completely superimposed on the nanoscale. The characterization results of the remaining embodiments are the same as the above results, all indicating that the Cu, N and C elements are evenly distributed throughout the carbon black, and Cu is evenly dispersed in a single-atom state.
[0044] Further, in order to test the catalytic performance of the copper-based single-atom catalyst prepared by the present invention, 1 mg of the catalyst samples prepared in Examples 1 to 3 were weighed and dissolved in 1 mL of slurry (isopropanol: water: naphthol = 480 μL: 480 μL: 40 μL). After sufficient ultrasonication, a uniform black solution was obtained, which was then smeared on a 1×2 cm carbon paper so that the catalyst loading was 0.5 mg / cm 2 The test was carried out in an H-type electrolytic cell, and a Nafion 117 proton exchange membrane was used to separate the cathode chamber from the anode chamber. The three-electrode system consists of a reference electrode Ag / AgCl electrode, a counter electrode platinum sheet, and a working electrode. The carbon paper of the working electrode was cut into a size of 1.0 cm × 1.5 cm, and the working area was 1 cm 2 (1.0cm×1.0cm).
[0045] Before the test, the three-electrode system was used to collect cyclic voltammetry curves to better activate the catalyst. Then, linear sweep voltammetry curves were collected at a scan rate of 5mV / s in the potential range of 0 to -1.6V vs.Ag / AgCl, and iR compensation was performed. The linear sweep voltammetry (LSV) test can intuitively show the changes in the LSV curves of adding 20mM HMF under different materials.
[0046] The LSV curves of the catalyst samples prepared in Examples 1 to 3 in a boric acid electrolyte containing 0.02 M HMF are shown in FIG. Figure 5 As shown by Figure 5 It can be seen that the catalyst sample Cu-NC-650 has a higher current density than the other two catalyst samples at the same potential, proving that it has the highest reduction activity.
[0047] The ECH conversion, selectivity and Faraday efficiency of HMF of the catalyst samples prepared in Examples 1 to 3 at a potential of -0.6 V vs. RHE are shown in Figure 6 As shown by Figure 6 It can be seen that the catalyst sample Cu-NC-650 has higher activity, and the Faradaic efficiency (FE) of BHMF is close to 90% at a potential of -0.6 V vs. RHE.
[0048] In summary, the copper-based single-atom catalyst prepared by the present invention has clear and uniform active centers and maximum metal utilization, can be used for electrocatalytic reduction of 5-hydroxymethylfurfural HMF to prepare 2,5-furan dimethanol DHMF, and has high reduction activity, selectivity and stability in actual catalytic reactions.
[0049] The technical solution of the present invention is not limited to the above-mentioned specific embodiments. All technical variations made according to the technical solution of the present invention fall within the protection scope of the present invention.
Claims
1. A method for preparing a copper-based single-atom catalyst, characterized in that: The following steps are involved: S1. Dissolve 1,10-phenanthroline and copper nitrate trihydrate in a molar ratio of 3:1 in 30 mL of anhydrous ethanol and stir thoroughly to form a uniform solution. Stir magnetically in a 50°C oil bath for 3 h. Then, add 0.0300 g of carbon black to the solution and continue stirring magnetically in a 50°C oil bath for 3 h. S2, removing ethanol from the sample obtained in step S1 and drying it, grinding the obtained solid powder into a uniform powder, calcining it at 550-750° C. for 2 h, and then cooling it to room temperature; S3. Etching the sample obtained in step S2 with a mixed acid solution to remove unstable metal particles, filtering, washing and drying the acid-washed solution to obtain a solid powder, calcining it at 550-750° C. for 2 hours, and then cooling it to room temperature to obtain a copper-based single-atom catalyst.
2. The method for preparing a copper-based single-atom catalyst according to claim 1, characterized in that: In the step S2, calcination is carried out in an argon calcination atmosphere with an argon flow rate of 60 sccm.
3. The method for preparing the copper-based single-atom catalyst according to claim 1, characterized in that: In the step S2, the temperature is increased to 550-750°C at a heating rate of 10°C / min.
4. The method for preparing a copper-based single-atom catalyst according to claim 1, characterized in that: The mixed acid solution is a mixed solution of hydrochloric acid and nitric acid in a molar ratio of 1:
2.
5. A copper-based single-atom catalyst prepared by the method according to any one of claims 1 to 4.
6. Use of the copper-based single-atom catalyst as claimed in claim 5 in the electrochemical reduction of 5-hydroxymethylfurfural HMF to prepare 2,5-furan dimethanol DHMF.